2018
DOI: 10.5194/acp-2017-1180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatiotemporal variability of NO<sub>2</sub> and PM<sub>2.5</sub> over Eastern China: observational and model analyses with a novel statistical method

Abstract: <p><strong>Abstract.</strong> Eastern China (27° N–41° N, 110° E–123° E) is heavily polluted by nitrogen dioxide (NO<sub>2</sub>), particulate matter with aerodynamic diameter below 2.5 μm (PM<sub>2.5</sub>) and other air pollutants. These pollutants var… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Another study involving 510,158 eczema visits reported that a 10 lg/m 3 increase in NO 2 (lag06) concentrations was associated with a 2.31% (95% CI: 1.17-3.45%) increase of outpatient visits (Li et al 2016). Liu et al (2016Liu et al ( , 2018a also observed that NO 2 concentrations were significantly associated with childhood atopic eczema and acne vulgaris in outpatients (Liu et al 2018b(Liu et al , 2016. A cross-sectional study conducted in France found that long-term exposure of NO 2 in children was significantly associated with lifetime eczema (Penard-Morand et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study involving 510,158 eczema visits reported that a 10 lg/m 3 increase in NO 2 (lag06) concentrations was associated with a 2.31% (95% CI: 1.17-3.45%) increase of outpatient visits (Li et al 2016). Liu et al (2016Liu et al ( , 2018a also observed that NO 2 concentrations were significantly associated with childhood atopic eczema and acne vulgaris in outpatients (Liu et al 2018b(Liu et al , 2016. A cross-sectional study conducted in France found that long-term exposure of NO 2 in children was significantly associated with lifetime eczema (Penard-Morand et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of urbanization, industrialization, and motorization, Chinese cities have been heavily polluted (Feng et al 2018;Wang et al 2018;Liu et al 2018a). According to the report on the State of the Ecology and Environment in China (http:// english.mee.gov.cn/Resources/Reports/soe/), in 2015-2018, the average concentrations of PM 2.5 , PM 10 , O 3 , SO 2 , NO 2 and CO were 47 lg/m 3 , 81 lg/ m 3 , 151 lg/m 3 , 20 lg/m 3 , 35 lg/m 3 , and 1.8 mg/m 3 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese official air quality monitoring network measures PM 2.5 and other pollutants since 2013, mostly in the urban areas. These data form the basis for many recent studies on the spatial and temporal characteristics of urban air pollution and their causes over China (Liu et al, 2018;Wang et al, 2014;Ge et al, 2018). However, these measurement data cannot be used to analyze long-term trends and variability of PM 2.5 and resulting health effects.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm the requirement of the third criterion, we apply Empirical Orthogonal Function (EOF) analysis. EOF is commonly used to decompose the data into spatial and temporal modes in earth science (Liu et al, 2018; Lorentz, 1956). The EOF spatial modes provide information about the areas where the modal activity is the highest, which correspond to the main energy distribution of a system (Cohen et al, 2003).…”
Section: Methodsmentioning
confidence: 99%